PERBEDAAN RESPON PASAR TERHADAP LABA - Vestari, Mekani (PRESTASI, 2013)
ABSTRACTÂ The aim of this research is to get an empirical evidence about the difference association between investor response toward earnings predictability for profitable firms and unprofitable firms. The population of this research is 163 manufacture firms which is listed in Indonesia Stock Exchange refer to Indonesian Capital Market Directory that require data for years 2005 until 2010. Based on purposive sampling method the sample in this research is for about 123 firms. The analysis uses CKSS model that represents Future Earnings Response Coefficient (FERC). Than the sample divided into two groups, consists of profitable firms and unprofitable firms to test by chow tests. The result shows that for profitable firms are significantly different with unprofitable firms of association between investor response to earnings predictability. Â Keyword : future earnings response coefficient, profitable firms, unprofitable firms, liquidation option